2021
DOI: 10.18632/aging.202886
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a mesenchymal-related signature associated with clinical prognosis in glioma

Abstract: Malignant glioma with a mesenchymal (MES) signature is characterized by shorter survival time due to aggressive dissemination and resistance to chemoradiotherapy. Here, this study used the TCGA database as the training set and the CGGA database as the testing set. Consensus clustering was performed on the two data sets, and it was found that two groups had distinguished prognostic and molecular features. Cox analysis and Lasso regression analysis were used to construct MES signature-based risk score model of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…1G and Supplementary Fig. S4 ), which is consistent with previous reports that these genes can overenhance or attenuate tumor growth [ 27 31 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1G and Supplementary Fig. S4 ), which is consistent with previous reports that these genes can overenhance or attenuate tumor growth [ 27 31 ].…”
Section: Resultssupporting
confidence: 91%
“…FCGR2A is a cell surface receptor on phagocytic cells, involved in the process of phagocytosis and clearance of immune complexes [ 40 ]. Silencing FCGR2A expression suppressed glioma proliferation, migration and invasion [ 31 ]. Collectively, the function of these genes in tumors, especially VAMP8 and FCGR2A in gliomas, has been fully demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, integrating multiple gene biomarkers into a single signature was adopted because the prediction accuracy of the signature can be enhanced compared to a single biomarker [ 48 ]. Previous studies have reported that this biomarker signature of gliomas, such as the autophagy-related signature [ 49 , 50 ], ferroptosis-related signature [ 51 ], and mesenchymal-related signature [ 52 ], has shown strong prognostic power. In addition, although an ERS-related signature has been reported, it is entirely different from ours, and too many genes to make up the signature results inconvenient and impractical in clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53] FCGR2A, CYBB, CXCL8 and ITGB2 were significantly upregulated in GBM and associated with shorter overall survival of GBM patients. [54][55][56][57][58] As for the role of CCR1 in GBM, the results are still controversial. Zhang et al found that CCR1 and CCR5 were two key receptors of CCL8 and they triggered CCL8-induced invasion of GBM cells, 59 while Pham et al reported that individual deletion of CCR1 or CCR5 had little or no effect on the survival of tumor-bearing mice, or the number of GBM-infiltrated microglia/macrophages and lymphocytes.…”
Section: Dovepressmentioning
confidence: 99%